The Urgency of Genetic Research in Humans - Trikusumaadi, Stefanus Khrismasagung; Dewi, Noviana; Widhiyastuti, Endang (GLOBAL HEALTH SCIENCE GROUP, 2024)
Genetic research is a breakthrough in the field of molecular biology which has been proven to contribute to health both in diagnosis and therapy. To support the achievement of these competencies, health students need to view the importance of genetic studies in humans. A person's understanding of a subject is greatly influenced by a person's cognition and the information they absorb. Using a survey approach to students and stakeholders of health science universities. The aim of this study to obtain an overview of health students' understanding of the urgency of genetic research in humans. The level of student understanding of the meaning of genetics is considered quite good with an average score of 2.10 on a scale of 0 – 3. Based on the assessment of various genetic research titles, students' understanding of the urgency of genetic research in humans is relatively high, with an average score of 3.19 on a scale of 1-4. There were no differences in student assessments regarding the urgency of genetic research in humans in each class. Significant differences based on generation appear in students' preferences for research on human genetics.